Effect of analytical parameters on the precision of soil zinc extraction methods - Pessôa da Cruz, Mara Cristina; Fessel Graner, Celso Augusto; Ferreira, Manoel Evaristo (Pesquisa Agropecuaria Brasileira, 1997)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} @font-face {font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} a:link, span.MsoHyperlink {color:blue; text-decoration:underline; text-underline:single;} a:visited, span.MsoHyperlinkFollowed {color:purple; text-decoration:underline; text-underline:single;} p {margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Fifteen soil samples and four extractants (DTPA, Na2EDTA, HCl and Mehlich 1) were used to study soil extraction methods for available zinc. Each extractant was studied in three soil: solution ratios (1:2, 1:4 and 1:10) and in three extraction periods in the ratio most frequently used. The zinc extracted by DTPA, Na2EDTA and HCl was not affected by use of soil: solution ratios 1:2 and 1:4, but the amount extracted increased with the 1:10 ratio. In this relation, the variation coefficients increased. With Mehlich, no definite tendency was observed. The increase of extraction period for DTPA extractant, in 1:2 ratio, had little effect on the amount of zinc extracted and on the precision. As to Na2EDTA extractant in 1:10 ratio, with the increase of extraction time, both increased. As to HCI and Mehlich, both in 1:4 ratio, the increase in extraction period had no effect on the amount of zinc extracted and no definite effect on the precision. Thus, the use of 1:2 ratio for DTPA and Na2EDTA and 1:4 ratio for acid extractants is recommended. Concerning the period of extraction, 120 min should be used with DTPA and Na2EDTA, 15 min with HCl and 5 min with Mehlich.